LAND ADMINISTRATION SYSTEM BASED ON THE VALUES OF JUSTICE - Gloria Gita Putri Ginting (International Journal of Society and Law, 2025)
A land administration system plays a critical role in ensuring legal certainty, equitable access, and responsible land management within a society. This study examines the concept and implementation of a land administration system founded on the values of justice, emphasizing fairness, transparency, and inclusiveness in land governance. By integrating principles of distributive, procedural, and restorative justice, the system aims to address long-standing issues such as land disputes, unequal land distribution, unclear ownership rights, and limited public participation. Using a qualitative descriptive approach supported by legal and policy analysis, this research evaluates the effectiveness of justice-based land administration practices in promoting social equity and strengthening public trust. The findings indicate that incorporating justice values into land administration processes—such as registration, certification, dispute resolution, and spatial planning—enhances accountability, reduces conflicts, and supports sustainable land use. The study concludes that a justice-oriented land administration system is essential for achieving balanced development, protecting community rights, and building a more equitable and harmonious land governance framework.